2004
DOI: 10.1210/er.2003-0015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Endocrine, and Genetic Mechanisms of Arterial Calcification

Abstract: Pathologists have recognized arterial calcification for over a century. Recent years have witnessed a strong resurgence of interest in atherosclerotic plaque calcification because it: 1) can be easily detected noninvasively; 2) closely correlates with the amount of atherosclerotic plaque; 3) serves as a surrogate measure for atherosclerosis, allowing preclinical detection of the disease; and 4) is associated with heightened risk of adverse cardiovascular events. There are two major types of calcification in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
217
1
24

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(245 citation statements)
references
References 691 publications
(315 reference statements)
3
217
1
24
Order By: Relevance
“…Aortic calcification reflects calcification in both the intimal and medial tunica layers of the artery, in contrast to coronary artery calcification, which generally occurs in the intimal layer of an atherosclerotic plaque 27. Medial calcification is not associated with atherosclerotic plaque, but is strongly associated with aging, diabetes, and end‐stage renal disease 28. Interestingly, in the current study, TACS and CACS demonstrated different prognostic roles in the elderly without obstructive CAD.…”
Section: Discussionmentioning
confidence: 49%
“…Aortic calcification reflects calcification in both the intimal and medial tunica layers of the artery, in contrast to coronary artery calcification, which generally occurs in the intimal layer of an atherosclerotic plaque 27. Medial calcification is not associated with atherosclerotic plaque, but is strongly associated with aging, diabetes, and end‐stage renal disease 28. Interestingly, in the current study, TACS and CACS demonstrated different prognostic roles in the elderly without obstructive CAD.…”
Section: Discussionmentioning
confidence: 49%
“…Ten‐year Framingham risk scores for CVD and death are related to 18 F‐NaF uptake 64. Other retrospective studies have shown positive correlations between arterial 18 F‐NaF uptake and CVD risk factors, including age, sex, hypertension, hypercholesterolemia, and diabetes mellitus, further supporting the notion that 18 F‐NaF PET imaging may improve CVD risk stratification 98, 100, 101, 102, 104, 111, 112, 113, 114…”
Section: Positron Emission Tomographymentioning
confidence: 81%
“…The exposed hydroxyapatite crystal surface area in the arterial wall and early active vascular calcification is below the resolution of CT, but the evolving powdery microcalcification is readily identified by 18 F‐NaF (Figure 3). 22, 98, 106 Dweck et al106 investigated histological markers of active calcification (ie, tissue nonspecific alkaline phosphatase and osteocalcin) in aortic stenosis and found a strong correlation between 18 F‐NaF uptake and these markers, thus confirming that 18 F‐NaF PET imaging provides information about the activity of calcification and might differentiate biologically active calcification from stable calcification. Alizarin Red staining also confirmed 18 F‐NaF uptake in areas of microcalcification17 (Figure 4).…”
Section: Positron Emission Tomographymentioning
confidence: 97%
See 2 more Smart Citations